Characterization of rapid-hardening alkali-activated binders incorporating basic oxygen furnace slag and blast furnace slag - Omur, Tarik; Miyan, Nausad; Ozkan, Hakan; Kabay, Nihat (ELSEVIER, 2025)
Basic oxygen furnace slag (BOFS), a byproduct of steel production, has limited commercial value due to its volumetric instability and inconsistent chemical reactivity, hindering its use in cementitious systems. While the alkali activation of BOFS has been explored, prior studies often lack detailed evaluation of its rapid-hardening potential and synergy with supplementary materials. To bridge this gap, this study introduces a structured methodology for producing rapidhardening alkali-activated pastes (AAPs) by progressively replacing blast furnace slag (BFS) with BOFS in 20 % increments up to 100 %. Each mixture was activated with 6M sodium hydroxide (NaOH) and sodium silicate at a silicate modulus of 0.8. This incremental design enabled a thorough assessment of BOFS incorporation on fresh-state behavior, thermal evolution, mechanical performance, and microstructural development across both early and later ages. The results reveal that BOFS-rich mixtures accelerated setting due to the formation of earlycrystallizing phases such as calcium-silicate-hydrate and hydrogarnet which contributed to enhanced early-age plasticity and reactivity. Notably, the AAP mixture containing 60 % BOFS achieved approximately a 150 % increase in compressive strength at 3 h and up to a 67 % increase at 6 h, compared to the reference paste containing 100 % BFS. Compressive strengths of 33.2-19.9 MPa at 1 day, 75.6-33.1 MPa at 7 days, and 90.3-48.0 MPa at 28 days were obtained with 20-80 % BOFS incorporation. These results demonstrate the potential of BOFS for highperformance, rapid-setting AAPs in time-critical applications, while promoting sustainable use of industrial byproducts.
Keywords: Basic oxygen furnace slag; Alkali-activated paste; Rapid hardening material; Early age strength; Microstructure; STEEL SLAG; BOF SLAG; HYDRATION; COMPOSITES; STRENGTH; MODEL; Construction & Building Technology; Engineering